Assessing the Local Biowaste Potential of Rural and Developed Areas Using GIS-Data and Clustering Techniques: Towards a Decision Support Tool - De Buck , Viviane; Sbarciog , Mihaela; Polanska , Monika; Van Impe, Jan F.M. (Frontiers in Chemical Engineering, 2022)
As the chemical and energy producing industries are steadily transitioning towards more sustainable processing practices, renewable biomass resources are becoming increasingly more valuable. Recently, following the realisation that renewable resources for the chemical and energy industry should not compete with food supplies, the use of plant-based biowaste has significantly gained in interest. Due to its inherently variable composition, diffuse distribution, and seasonality, it is of the utmost importance that (potential) biorefinery exploiters are well informed of the biowaste resources that are available in the vicinity of their (planned) biorefinery. Designing a biorefinery in such a way that it can tailor for the locally available biowaste resources, exhibits several compelling advantages. Apart from significantly reduced logistics costs, the usage of local biowaste can be a reciprocal advantage for both the involved community and the biorefinery. In this paper, a GIS-based (Geo-Information System) bio-inventory toolbox is presented. The toolbox is developed to aid the biorefinery designers and decision makers, e.g., governmental bodies, to get an adequate overview of the locally available plant-based biowaste resources and, linked to this, the expected periodical amounts, their composition, and their seasonality. The toolbox presented in this contribution is the first part of a decision support tool for the development of a locally embedded flexi-feed and small-scale biorefinery, additionally consisting out of a process modelling tool, and an optimisation tool. Both of these additional tools will employ the information obtained from the bio-inventory toolbox to simulate and optimise several suitable biorefinery designs. The eventual goal of the decision support tool is to provide users with several optimised biorefinery designs that are tailored for their local setting. The additional toolboxes are detailed elsewhere.